Efektivitas Teknik Role Play untuk Menurunkan Perilaku Agresivitas Anak di Sekolah - Widyorini, Endang; Ismawan, Shabrina Aprililita (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
The study aimed to use role-play techniques to determine aggressive behavior in physical aggression (hitting and pushing) and verbal aggression (teasing and yelling) by children toward other children. The study used a quasi-experimental method, with a single case, with an A-B-A design, then this data was processed with descriptive analysis and hypothesis testing with a pre-post-test design, with a comparative test of baseline scores one and 2. Processing with hypothesis testing with Wilcoxon signed test. Participants in the study were six boys aged 9-11 years (M = 10.9, SD 1.2) and students in grades 4-5 SD. The results of the descriptive analysis above show a decrease in aggressive behavior scores at each stage of the intervention, both physical and verbal aggressiveness. The results of testing the hypothesis using the analysis program SPSS Wilcoxon Signed Rank Test showed a Z value of -3.066 at a significance level of p <.001. This means that the hypothesis is accepted, meaning there is a significant decrease in the scores of aggressive behavior before and after the intervention with the role-play technique.